PERANCANGAN SISTEM OTOMATISASI PENGUKURAN PH PADA TANAMAN HIDROPONIK - Damayanti, Eva; Yurika, Yurika; Fauzan, Fadhil (Jurnal TEDC; Vol 18 No 2 (2024): JURNAL TEDC, 2024)
Agriculture is a very important part of society in Indonesia. Agriculture is still a source of income for some people because most areas in Indonesia are agricultural land. To develop the results of agricultural land, but many agricultural lands have been converted. There is another way for people to utilise the narrow lands around the neighbourhood with the use of hydroponic planting method. Hydroponics is one of the modern methods of farming without using soil but using water by emphasising the fulfilment of nutrients and pH regulation in plants. This research aims to know and understand the characteristics of each tool that will be used. Measuring pH by using an automation system on hydroponic plants. Therefore, it is necessary to make innovations to the measurement of pH in hydroponic plants using an automation system. Controlling pH can be done manually using a pushbutton and automatically by determining the setpoint compared to the sensor reading. In a manual way we can adjust the pH level as desired by pressing the pushbutton either to increase the pH value or decrease the pH value. But in the automatic running system we only need to determine the setpoint used, in this system <7 then the pH up pump will turn on>7 then the pH down pump will turn on if =7 then both pumps will be in a state of not turning on. The components that can support this system are of course the sensor as a reader of the pH value, and the microcontroller as processing the pH data on the sensor then giving commands to the actuator, and of course the actuator is a pump. Automation of pH in hydroponics is certainly very effective and efficient compared to the manual method where we must always monitor directly, check directly, and control the pH value directly. But in the pH system automation everything can be done only through a smartphone.